2015
DOI: 10.1007/s00262-015-1721-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility to cervical squamous cell carcinoma is associated with HLA-DPB1 polymorphisms in Taiwanese women

Abstract: Cervical cancer is a multifactorial disease, and increasing evidence suggests that host immunogenetic background may contribute to its pathogenesis. Genetic variations in human leukocyte antigen (HLA) genes may alter the efficiency of immune response to human papillomavirus (HPV) antigens and have been implicated in the risk of cervical cancer. We investigated whether polymorphisms in the HLA-DPB1 gene were associated with cervical cancer risk in a Taiwanese population. HLA-DPB1 alleles and +550 G/A polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Hu et al reported, for the first time, that genetic variants in the HLA-DP/DQ loci might be marker polymorphisms for both HBV infection and risk of developing HCC 44. HLA-DPB1 polymorphisms increased the risk for cervical squamous cell carcinoma in Taiwanese women 45.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al reported, for the first time, that genetic variants in the HLA-DP/DQ loci might be marker polymorphisms for both HBV infection and risk of developing HCC 44. HLA-DPB1 polymorphisms increased the risk for cervical squamous cell carcinoma in Taiwanese women 45.…”
Section: Discussionmentioning
confidence: 99%
“…We also investigated whether HLA-DPB1 alleles are associated with cervical cancer risk in the Japanese population, because this association was found to be significant in Chinese and Taiwanese populations. [12][13][14] …”
Section: Introductionmentioning
confidence: 98%
“…The biological involvement of HLA-DPB is mainly in the immune response. HLA-DP is participates in the origin and development of cervical cancer, and different HLA-DP polymorphisms correspond to different cervical cancer risks in the Chinese and Swedish populations [51]. Genetic polymorphism of HLA-DP is also associated with the prognosis of Hodgkin's lymphoma [52].…”
Section: Discussionmentioning
confidence: 99%